Regionalization of Slovenia By Establishing Functional Regions - Šnajder, Leonida; Bobek, Vito (Naše gospodarstvo/Our economy, 2014)
Slovenia is a country with a plurality of municipalities that are (in most cases) too small in terms of development and in need of more inducements for tourism, greater investment opportunities, and the establishment of shopping and logistics channels. Of Slovenia’s 212 municipalities, 111 do not meet the statutory minimum level for the establishment of a municipality, which is reflected in the uneven development in vari- ous parts of the country. A similar problem has been faced by other countries (e.g., Austria), but they have resolved this problem to a satisfactory level, particularly by applying the concept of functional networking. The design and development of uni- form regions, their connectedness, and their openness to cross-border cooperation are all crucial for the effective development of Slovenia as a whole, which will sti- mulate regional development based on functional integration. The purpose of this article is to examine whether it is possible to establish a functional region in Slove- nia; we will explore the legal foundations, methods, and effects of such an establi- shment.